Thinking Through Monuments: Levantine Monuments as Technologies of Community-Scale Motivated Social Cognition. Issue 3 (August 2021) - Hogue, Timothy
Abstract : This study proposes that monuments are technologies through which communities think. I draw on conceptual blending theory as articulated by Mark Turner and Gilles Fauconnier to argue that monuments are material anchors for conceptual integration networks. The network model highlights that monuments are embedded in specific spatial and socio-historical contexts while also emphasizing that they function relationally by engaging the imaginations of communities. An enactivist understanding of these networks helps to explain the generative power of monuments as well as how they can become dynamic and polysemic. By proposing a cognitive scientific model for such relational qualities, this approach also has the advantage of making them more easily quantifiable. I present a test case of monumental installations from the Iron Age Levant (the ceremonial plaza of Karkamiš) to develop this approach and demonstrate its explanatory power. I contend that the theory and methods introduced here can make future accounts of monuments more precise while also opening up new avenues of research into monuments as a technology of motivated social cognition that is enacted on a community-scale.